Perinatal and Crowding-Related Risk Factors for Invasive Pneumococcal Disease in Infants and Young Children: A Population-Based Case-Control Study - Hjuler, Thomas; Wohlfahrt, Jan; Simonsen, Jacob; Kaltoft, Margit S.; Koch, Anders; Kamper-Jørgensen, Mads; Biggar, Robert J.; Melbye, Mads (Clinical infectious diseases, 2007)
Background. Denmark's systems of registry-based data offer a unique opportunity to examine, on a population basis, risk factors for invasive pneumococcal disease (IPD) relating to perinatal and crowding exposures among children. The main objective of this study was to identify the role of familial and day care factors in the risk of IPD among unvaccinated infants and children. Methods. A total of 1381 children aged 0–5 years old who experienced IPD were identified from a national surveillance program of IPD in Denmark. Risk factors were assessed in a matched, nested, case-control study that assigned 10 population control subjects to every case patient. Exposure information was obtained from several population-based, person-identifiable Danish registries. Results. Preterm birth and low birth weight significantly increased the risk of IPD among infants. In infants 0–5 months of age, the risk of IPD was high among infants who had older siblings, compared with infants of the same age who had no older siblings (adjusted rate ratio [aRR], 3.38; 95% confidence interval, 2.11–5.42), whereas the aRR was low (aRR, 0.56; 95% confidence interval, 0.47–0.65) in children aged 6–23 months. Day care attendance, compared with home care, increased the aRR of IPD 0–2 months after enrollment in a day care program (aRR, 2.28; 95% confidence interval, 1.73–3.00), whereas the aRR was 0.70; (95% confidence interval, 0.46–1.06) ≥6 months after enrollment in children aged 6–23 months. Conclusions. During infancy (age, 0–6 months), risk of IPD is associated with low birth weight, presumably because of lower levels of passively acquired maternal antibody. During early childhood, exposure to other young children (either siblings or through day care attendance) is clearly associated with IPD, but natural exposure appears to occur rapidly and confer durable immunity.